Over-Expression of Hypochlorite Inducible Major Facilitator Superfamily (MFS) Pumps Reduces Antimicrobial Drug Susceptibility by Increasing the Production of MexXY Mediated by ArmZ in Pseudomonas aeruginosa - Dulyayangkul, Punyawee; Satapoomin, Naphat; Avison, Matthew B.; Charoenlap, Nisanart; Vattanaviboon, Paiboon; Mongkolsuk, Skorn (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa, a well-known cause of nosocomial infection, is frequently antibiotic resistant and this complicates treatment. Links between oxidative stress responses inducing antibiotic resistance through over-production of RND-type efflux pumps have been reported in P. aeruginosa, but this has not previously been associated with MFS-type efflux pumps. Two sodium hypochlorite (NaOCl) inducible MFS efflux pumps encoded by mfs1 and mfs2 were selected for study. Antibiotic susceptibility testing was used to define the importance of these MFS pumps in antibiotic resistance and proteomics was used to characterize the resistance mechanisms involved. The results revealed that mfs1 is NaOCl inducible whereas mfs2 is NaOCl, N-Ethylmaleimide and t-butyl hydroperoxide inducible. Deletion of mfs1 or mfs2 did not affect antibiotic or paraquat susceptibility. However, over-production of Mfs1 and Mfs2 reduced susceptibility to aminoglycosides, quinolones and paraquat. Proteomics, gene expression and targeted mutagenesis showed that over-production of the MexXY RND-type efflux pump in a manner dependent upon armZ, but not amgRS, is the cause of reduced antibiotic susceptibility upon over-production of Mfs1 and Mfs2. mexX expression analysis in strains carrying various lengths of mfs1 and mfs2 revealed that at least three transmembrane domains are necessary for mexX over-expression and decreased antibiotic susceptibility. Changes in paraquat susceptibility were independent from mexX and armZ suggesting that it is a true substrate of Mfs1 and Mfs2. Altogether, this is the first evidence of cascade effects where the over-production of an MFS pump causes over-production of an RND pump, in this case MexXY via increased armZ expression.